MiR-29a: a potential therapeutic target and promising biomarker in tumors. Issue 1 (8th February 2018) - Wang, Jin-yan; Zhang, Qian; Wang, Dan-dan; Yan, Wei; Sha, Huan-huan; Zhao, Jian-hua; Yang, Su-jin; Zhang, He-da; Hou, Jun-chen; Xu, Han-zi; He, Yun-jie; Hu, Jia-hua; et al.
Abstract : MiRNAs, small non-coding RNA molecules, were recognized to be associated with the incidence and development of diverse neoplasms. MiRNAs were small non-coding RNAs that could regulate post-transcriptional level by binding to 3′-UTR of target mRNAs. Amongst which, miR-29a was demonstrated that it had significant impact on oncogenicity in various neoplasms through binding to critical genes which enhanced or inhibited the progression of cancers. MiR-29a participated in kinds of physiological and pathological processes, including virus replication, cell proliferation, differentiation, apoptosis, fibrosis, angiogenesis, tumorigenicity, metastasis, drug-resistance, and so on. According to its sufficient sensitivity and specificity, many studies showed that miR-29a might serve as a potential therapeutic target and promising biomarker in various tumors. In this review, we discussed the functions of miR-29a and its potential application in the diagnosis, treatment and stages of carcinoma, which could provide additional insight to develop a novel therapeutic strategy.